Analysis of Slope Stability Due to Variations in Slope and Soil Characteristics Using the Slope Mass Rating (SMR) Method in Sorong Regency - Rokhman Rokhman; Jeane Akerina; Ahmad Januar Jafaruddin; Retno Puspa Rini (Sean Institute, 2025)
Sorong Regency experiences high rainfall in certain months, especially in the Katapop area, so slope stability is one of the important factors related to soil characteristics and slopes that cause landslides. Previously, it was known that there are many models for analyzing slope stability, one of which is Slope Mass Rating (SMR), which is usually used on rocky slopes. However, this study will analyze the level of slope stability on soil slopes with modified parameters. The purpose of this study is to analyze slope stability in the Katapop area through an analysis of the influence of slope inclination and soil characteristics using the Slope Mass Rating (SMR) approach and comparing the results with the Safety Factor (SF) values from the Bishop method in GeoSlope to assess the feasibility of using modified SMR as an alternative method. The data collection technique used a handboring tool. The results of the study show that the potential for landslides in Katapop is influenced by slope inclination, soil composition, and water content, which affect the SMR value and slope stability. Validation using the Bishop method in GeoSlope is in line with the SMR classification results.